Timing of Strobilurin Fungicide for Control of Top Dieback in Corn - Eric Adee; Stu Duncan (Kansas Agricultural Experiment Station Research Reports, 2016)
Significant yield losses can result from top dieback (TDB) in dent corn (Zea mays), which is caused by infection by the fungus causing anthracnose (Colletotrichum graminicola). Research is limited on the effectiveness of fungicide application because of the unpredictable nature of the disease. Two field studies were established to assess the timing of fungicide application on TDB, one in Illinois (2010) and the other in Kansas (2015). Fungicide applications at tasseling (VT) and later were effective in reducing the incidence of TDB 20 to 30% and increasing yield 15 to 19 bu/a, or up to 10%, while earlier applications (V5 to V8) did not reduce TDB nor increase yield compared to the untreated check.
Keywords: Top Dieback; corn; strobilurin; fungicide; Anthracnose